Sosialisasi Program Pembinaan Wirausaha Mahasiswa (P2MW) dan Pelatihan Pembuatan Propasal bagi Mahasiswa - Setiawan, Ito; Serli, Serli; Maulida, Farah Mei; Setyaningsih, Gustin; Pramono, Agus; Riyanto, Riyanto (Universitas Pahlawan Tuanku Tambusai, 2024)
P2MW is very suitable in achieving the vision of Amikom University Purwokerto. The number of P2MW proposals submitted in 2023 to the student affairs section still has not met the target set at 50 proposals. Based on the number of proposals funded in 2023, there are 7 proposals, this still does not meet the target set by the student affairs department, amounting to more than 10 funded proposals. This target is still far from student expectations. In order for a proposal to be funded by the Ministry, the proposal needs to comply with existing guidelines such as writing templates, business objectives, potential consumers, products, resources, marketing and finance. The Student Affairs Department of Amikom University Purwokerto also has a target that in 2024 there will be proposals funded up to the national KMI EXPO with 3 teams, because KMI EXPO is a prestigious event at the national level. The methods used are lectures, questions and answers, pitching proposals and direct practice. The result of outreach and training is an increase in the number of proposals that pass the internal campus stage.